Treatment Effectiveness for Symptoms of Patulous Eustachian Tube: A Systematic Review. Issue 10 (December 2015) - Luu, Kimberly; Remillard, Andrew; Fandino, Marcela; Saxby, Alexander; Westerberg, Brian D.
Abstract : Objectives: To determine the effectiveness of currently available medical and surgical interventions for treating symptoms of Patulous Eustachian Tube (PET). Data Sources: A comprehensive search of MEDLINE (January 1948 to July 8, 2015), EMBASE (January 1974 to July 8, 2015), gray literature, hand searches, and cross-reference checking. Study Selection: Original published reports evaluating an intervention to treat the symptoms of patulous eustachian tube in patients 18 years and older. Data Extraction: Quality-of-case reviews were assessed with the National Institute of Health (NIH) Quality Assessment Tool for Case Series Studies. Data Synthesis: The search strategy identified 1, 104 unique titles; 39 articles with 533 patients are included. The available evidence consists of small case series and case reports. The most common medical treatment was nasal instillation of normal saline. Surgical treatments were categorized as mass loading of the tympanic membrane, eustachian tube plugging, and manipulation of eustachian tube musculature. Conclusions: The available evidence for management of patients with PET is poor in quality and consists predominantly of small case series. Further research is needed to determine the comparative efficacy of the current treatments.